Protective Factors of Nurses' Mental Health and Professional Wellbeing During the COVID-19 Pandemic: A Multicenter Longitudinal Study - Jonathan Jubin; Line Martin; Naomi Kabwiku; Philippe Delmas; Ingrid Gilles; Annie Oulevey Bachmann; Claudia Huber; Marie-Chantal Loiselle; Jessica Rassy; Francisco Sampaio; Francisco Sampaio; Ricardo Salgado; et al. (Frontiers Media S.A., 2024)
ObjectiveUsing a salutogenic approach, this study aimed to identify similarities in the protective factors of nurses' psychological Quality of Life (QoL) and professional wellbeing (PWB) in four countries and to assess their variability over time during the COVID-19 pandemic.MethodsThis multicentric study used a longitudinal design with three measurements points: Autumn 2021, spring 2022, and autumn 2022. The study consisted in a self-administered online questionnaire addressed to nurses working in hospitals. Across all measurement times, 3,310 observations were collected in France, 603 in Switzerland, 458 in Portugal, and 278 in Canada. The outcomes were psychological QoL and PWB, and several potential protective factors were used as determinants.ResultsAnalyses revealed few changes over time in the outcomes. Across all countries, psychological QoL was associated positively with resilience and perceived social support, whereas PWB was associated positively with the ability to provide quality work and support from colleagues and superiors.ConclusionThe findings of this study highlighted the potential of several factors protective of nurses' psychological QoL and PWB. These should be fostered through policies and measures to support nurses.